A Preliminary Study On The Legal Framework Of Solid Waste Management In Malaysia - Wan Siti Adibah Wan Dahalan; Zulkifli Mohd Nopiah; Intan Nadia Ghulam Khan (Medwell Journals, 2024)
Sustainable solid waste management is one of the main environmental challenges faced by many countries and legislation plays an important role as an instrument to implement it. The lack of a policy and legal framework is among the factors that contribute to an ineffective sustainable solid waste management. This study presents a preliminary study on the legal framework for household solid waste management and explores the issues and challenges that stand in the way of Malaysia's objective to establish a waste management system which is holistic, integrated, cost effective, sustainable and acceptable to the community as stated in its national solid waste management policy. The study shows that although Malaysia has her own legal framework for such a purpose, the lack of uniformity of the solid waste and public cleansing management Act 2007 (Act 672) for all states pose a challenge in the implementation of a solid waste management policy.